PENGARUH INSENTIF DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT SECURINDO PACKATAMA INDONESIA CABANG PLAZA PONDOK INDAH - Okky Herdiansyah (Al Hasanah Barokah Foundation, 2025)
This study aims to determine the effect of incentives and work motivation on employee performance partially and simultaneously at PT. Securindo Packatama Indonesia branch of Plaza Pondok Indah, South Jakarta. This method uses quantitative analysis methods, with a population of 46 employees. The sampling method used in this research is saturated sample, data analysis technique uses descriptive analysis, classical assumption test, regression test, correlation test, coefficient of determination test, and hypothesis test. incentives and work motivation have a simultaneous effect on employee performance with the regression equation Y = 6.834 + 0.465 X1 + 0.381 X2. The correlation coefficient value obtained is 0.700, meaning that the independent variable and the dependent variable have a very strong relationship with a coefficient of determination or simultaneous influence of 49% while the remaining 51% is influenced by other factors. Statistical test results F have a probability of 0.000 <0.05 or an Fcount value of 20,636 > Ftable 3.21. Thus H0 is rejected and Ha is accepted. This means that it is proven that there is a significant effect simultaneously between incentives (X1) and work motivation (X2) on employee performance (Y).